2015
DOI: 10.1002/sm2.65
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Therapies for Management of Premature Ejaculation: A Systematic Review

Abstract: IntroductionPremature ejaculation (PE) is defined by short ejaculatory latency and inability to delay ejaculation causing distress. Management may involve behavioral and/or pharmacological approaches.AimTo systematically review the randomized controlled trial (RCT) evidence for behavioral therapies in the management of PE.MethodsNine databases including MEDLINE were searched up to August 2014. Included RCTs compared behavioral therapy against waitlist control or another therapy, or behavioral plus drug therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 25 publications
0
59
1
2
Order By: Relevance
“…Psychotherapy involve education both patients and their partners,which may improve their sexual skills and increase self-confidence and reduce anxiety during sex [7].However, the majority of studies aim to treat PE by psychotherapy didn't meet the criteria for high level evidence based studies [8].The effectiveness of behavior therapy reported was different, with poor compliance of the patient.Although their utility are limited today, they are used to treat PE combined with drugs [9]. Surgical therapy such as ablation and modulation of dorsal penile nerve [10] is an innovative modality need further study and may cause irreversible damage which limit its clinical application.Circumcision seems to have some role in treating PE which can extend the ejaculation time [11],but it could not be interpreted as a justification for circumcision in men with PE even there were no adversely affect ejaculatory function [12].Although drug therapy is widely used for the treatment of PE in clinic, few studies devote to on-demand use of dapoxetine to treat LPE.…”
Section: Resultsmentioning
confidence: 99%
“…Psychotherapy involve education both patients and their partners,which may improve their sexual skills and increase self-confidence and reduce anxiety during sex [7].However, the majority of studies aim to treat PE by psychotherapy didn't meet the criteria for high level evidence based studies [8].The effectiveness of behavior therapy reported was different, with poor compliance of the patient.Although their utility are limited today, they are used to treat PE combined with drugs [9]. Surgical therapy such as ablation and modulation of dorsal penile nerve [10] is an innovative modality need further study and may cause irreversible damage which limit its clinical application.Circumcision seems to have some role in treating PE which can extend the ejaculation time [11],but it could not be interpreted as a justification for circumcision in men with PE even there were no adversely affect ejaculatory function [12].Although drug therapy is widely used for the treatment of PE in clinic, few studies devote to on-demand use of dapoxetine to treat LPE.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review included three randomised controlled trials (RCTs; n=82) of behavioural techniques among men with primary premature ejaculation 17. One study found no significant difference between behavioural techniques and a waiting list control group.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Developed by Semans in 1956, the “start–stop” technique involves stimulating the penis until one feels the urge to ejaculate, then removing the stimulation until the urge to ejaculate subsides . By repeating this maneuver multiple times before allowing oneself to ejaculate, the “start–stop” technique allows the patient to improve control over the ejaculatory response by learning to identify the physical and emotional parameters involved in arousal . Although once considered the gold standard for the treatment of PE, the “start–stop” technique has been under scrutiny, as recent studies disagree on the effectiveness of this behavioral‐based treatment .…”
Section: Current Therapiesmentioning
confidence: 99%
“…However, the authors failed to include a placebo arm to the trial, so the total effect of pelvic floor rehabilitation is undetermined . Pelvic floor rehabilitation also improves the quality of erections and increases the intracavernosal pressure . Some or all of the improvement in PE could be due to a concomitant improvement in ED .…”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation